2017
DOI: 10.24891/ni.13.12.2200
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating the Russian regions through an econometric analysis by socio-economic indicators influencing the consumer demand

Abstract: Ключевые слова: социально-экономические показатели, потребительский спрос, корреляционнорегрессионный анализ, структурные уравнения, кластерный анализ Аннотация Предмет. Зависимости между региональными социально-экономическими показателями и объемом различных видов кредитов для физических лиц, совокупный портфель которых выступает одной из институциональных детерминант потребительского спроса. Рассмотрение широкого набора характеристик для поиска оптимальных форм взаимодействия и согласования интересов государ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Please refer to the research indicated herein [5] for information about using econometric methods to verify socio-economic relationships and probability of mutual effect by evaluating the elasticity. In this case, we confine ourselves to the given equations: The above computations allow us to conclude that the a-offset is negative.…”
Section: The Analysis Of Variables Was Guided By the Following Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Please refer to the research indicated herein [5] for information about using econometric methods to verify socio-economic relationships and probability of mutual effect by evaluating the elasticity. In this case, we confine ourselves to the given equations: The above computations allow us to conclude that the a-offset is negative.…”
Section: The Analysis Of Variables Was Guided By the Following Assumptionsmentioning
confidence: 99%
“…The methodological framework of the so called direct costing system is the segregation of all costs, which is understood with a certain approximation, into variable VC (production and non-production depending on business performance, including changes in production output and uneven dynamics 4 , and fixed FC, that do not depend on the production output (or depend insignificantly) 5 . Mostly, direct costs are variable, while indirect ones can be both variable and fixed.…”
Section: Introductionmentioning
confidence: 99%